KOMPONEN PEMBELAJARAN PROGRAM LITERASI BUDAYA DI ECO BAMBU CIPAKU - Ari Putra; Jajat S Ardiwinata; Viena Rusmiati Hasanah (Jurnal Pendidikan dan Kebudayaan, 2018)
This study aims to analyze the learning components developed by the Cipaku ECO Bamboo institution, from learning devices, teaching materials and learning methods. Qualitative method used in this study and data collected by interviews, document analysis, and observation. Then, it processed by using triangulation techniques. It’s results revealed that the Cipaku ECO Bamboo institution makes the learning component in accordance with the learning needs of the community. The component is made in the form of a facilitator’s guide for traditional game learning devices containing the value of character education and functioning as learning  direction in accordance with learning signs. The use of expository learning methods in the form of lectures and question and answer is a model used by facilitators to transfer  knowledge of cultural literacy based on traditional games. Thus, the innovation in cultural literacy learning developed at ECO Bambu Cipaku is in the form of a learning device serving as guidance to the learning process of traditional games even though cultural literacy programs through traditional game learning do not yet have special competency standards in the implementation process